2016
DOI: 10.1073/pnas.1611581113
|View full text |Cite
|
Sign up to set email alerts
|

Schizosaccharomyces pombe kinesin-5 switches direction using a steric blocking mechanism

Abstract: Cut7, the sole kinesin-5 in Schizosaccharomyces pombe, is essential for mitosis. Like other yeast kinesin-5 motors, Cut7 can reverse its stepping direction, by mechanisms that are currently unclear. Here we show that for full-length Cut7, the key determinant of stepping direction is the degree of motor crowding on the microtubule lattice, with greater crowding converting the motor from minus enddirected to plus end-directed stepping. To explain how high Cut7 occupancy causes this reversal, we postulate a simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 42 publications
11
70
0
Order By: Relevance
“…During the revisions of this manuscript, it has been reported that the S. pombe kinesin-5 Cut7 switches directionality as a result of MT crowding by motile or non-motile proteins (Britto et al, 2016). This property of Cut7, and the ability of Cin8 to switch directionality by motor-clustering reported here, may result from a similar control mechanism, pointing to generality of the reported phenomena.…”
Section: Note Added In Proofsupporting
confidence: 66%
“…During the revisions of this manuscript, it has been reported that the S. pombe kinesin-5 Cut7 switches directionality as a result of MT crowding by motile or non-motile proteins (Britto et al, 2016). This property of Cut7, and the ability of Cin8 to switch directionality by motor-clustering reported here, may result from a similar control mechanism, pointing to generality of the reported phenomena.…”
Section: Note Added In Proofsupporting
confidence: 66%
“…Another possibility may involve cooperativity among multiple motors in a traffic jam due to slow stepping, which was also previously suggested for cut7, the S. pombe ortholog (Britto et al, 2016).…”
Section: Discussionmentioning
confidence: 55%
“…We have hypothesized previously that Cin8's super-stoichiometric binding occurs via both noncanonical binding and dimerization of the motor domains (14). There have also been two different mechanisms found to affect bidirectionality in kinesin-5 motors: a clustering model (33) and a crowding model (9,26). We hypothesize that the two different mechanisms of super-stoichiometric binding are involved in different mechanisms of regulating bidirectionality.…”
Section: Loop-8 Insert From Kip1 Was Insufficient For Super-stoichiommentioning
confidence: 89%
“…4 and 5). We hypothesize that this stoichiometric binding was caused by the large MBP tag inhibiting the superstoichiometric binding because of steric hindrance (26).…”
Section: Eg5-cl8mentioning
confidence: 99%